The concept of Pedagogical Content Knowledge in light of a neuroeducational perspective in initial teacher education - Albanese, Martina; Fiorello, Elisabetta (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
The construct of Pedagogical Content Knowledge (PCK), introduced by Lee Shulman in 1986, defines a distinctive form of professional knowledge that integrates disciplinary understanding with pedagogical expertise. It constitutes the theoretical core of the signature pedagogy of teaching—that is, the specific mode through which teacher professionalism is expressed and enacted in educational practice. In recent years, a new line of research has emerged aimed at exploring the intersection between the PCK construct and the principles of educational neuroscience, with the goal of deepening our understanding of the cognitive and functional foundations underlying teacher professional development (Cui & Zhang, 2021; Uden & Sulaiman, 2025). However, this body of work has yet to systematically address the specific relationships between the individual dimensions of PCK and the neurocognitive processes involved, nor does it provide actionable guidance for translating these principles into concrete strategies for initial teacher education. Building on these premises, the present contribution seeks to pursue a twofold objective: first, to provide a theoretical mapping of the neural networks and cognitive functions associated with the four dimensions of PCK identified by Magnusson and colleagues (1999)—namely, knowledge of curricula, knowledge of students’ understanding, knowledge of instructional strategies, and knowledge of assessment; and second, to identify the core professional competencies which, in alignment with these dimensions and their underlying cognitive mechanisms, are essential for the initial training of teachers.